Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Quick question. I'm given a set of logical statements:

1) $l \lor s$
2) $\lnot c$
3) $l \rightarrow b$
4) $s \rightarrow c$
5) $s \rightarrow \lnot w$

Now $l, s, c, b$ and $w$ represent certain statements. I won't type out what they are since it's not important for what I'm asking, but suffice to say that the question wants us to deduce that:

$\lnot c \rightarrow \lnot s$ by Modus Tollens (4) (and $\lnot c$ is in (2))
$\therefore l$ (Disjunctive Syllogism of (1)
$\therefore b$ (Modus Ponens and (4))

Which when I read through it makes perfect sense.

But see (5). When we get to deducing $\lnot s$ can we not assume $\lnot s \rightarrow w$ therefore deducing $w$?

share|cite|improve this question
As for the question in the title: no, it doesn't. As for the question in the body, I don't follow at all. What does (5) have to do with anything? In particular, as you have already deduced $\lnot s$, (5) plays no further role in any deduction (besides possibly deducing a contradiction, but that's not the case here either). – Marek Jun 18 '11 at 13:06
If it is sunny, it doesn't rain. But if it doesn't rain, it doesn't mean it has to be sunny. --Edit: ah, I hadn't seen Didier's answer below ;P – Bruno Stonek Jun 18 '11 at 14:57
There is a Wikipedia article on this fallacy: – Jonas Meyer Jun 20 '11 at 1:04
up vote 8 down vote accepted

You cannot go from S implies not W to not S implies W. You can use truth tables to validate this. What you can do is use contraposition and go from S implies not W to W implies not S.

So $P \Rightarrow Q \not\equiv \neg{}P \Rightarrow \neg{}Q$

But $P \Rightarrow Q \equiv \neg{}Q \Rightarrow \neg{}P$

share|cite|improve this answer
I'm not sure how to LaTeX this because this really is my first reply on a stack exchange website :-) – user12205 Jun 18 '11 at 13:05
@Jeroen: welcome! If you already know how to use LaTeX, then just enclose the mathematics expressions in dollar signs. For example: enclosing S \implies \neg W between a pair of dollar signs give $S\implies \neg W$. – Willie Wong Jun 18 '11 at 13:08
Oh, so it just works like regular inline equations :-) I tried that but I got no result in the WYSIWYG. I guess it gets parsed when you hit the add comment button! Thanks. – user12205 Jun 18 '11 at 13:11
@Jeroen: it didn't work in the WYSIWYG (preview pane)? It is supposed to, though sometimes it take about 5 seconds to start parsing. If it doesn't work, please drop a note on meta including your operating system and web browser of choice. Thanks! – Willie Wong Jun 18 '11 at 13:19
@Willie: I thought the preview pane was only for answers and not comments. Do you really have a preview pane for the comments? – JavaMan Jun 18 '11 at 16:02

Example: s = It is midnight, w = The sun shines.

More seriously, an easy way is to reduce everything to elementary statements. Here "p implies q" is equivalent to "not-p or q" hence "s implies not-w" is equivalent to "not-s or not-w" while "not-s implies w" is equivalent to "s or w" and these are not equivalent.

share|cite|improve this answer

I just wanted to clarify what you were able to deduce and chime in with the others about your question.

The premises you're working with:

1) $l \lor s$
2) $\lnot c$
3) $l \rightarrow b$
4) $s \rightarrow c$
5) $s \rightarrow \lnot w$

You mention that the exercise you were working with "wants us to deduce" some statements; first you start with

$\lnot c \rightarrow \lnot s\quad$ by Modus Tollens (4) (and $\lnot c$ is in (2))

  • This should probably be written as two steps (as in 6, 7 below). (See 6, 7, 8, 9 based on your logic, with additional justifications.)

6) $\;\lnot c \;\rightarrow \;\lnot s \quad$ (Modus Tollens, 4)
7) $\;\lnot s\;\qquad\qquad\quad$ (Modus Ponens, by (2) & (6))
8) $\;\therefore \;l\qquad\qquad\quad$ (Disjunctive syllogism of (1) & (7))
9) $\;\therefore \;b\qquad\qquad\quad$ (Modus ponens by (4) & (8))

I realize the question in your post didn't concern your deduction of the above steps, but I just wanted to make sure you weren't taking "shortcuts" and possibly omitting a step and references to previous statements used to justify those statements.

Now, note that, up to this point premise (5) is irrelevant/superfluous to your conclusions above...

You knew that it was appropriate and smart to apply Modus Tollens to conclude statement 6) above; I'm assuming now that others have clarified your question, you realize that given $\lnot s$, one cannot apply Modus Tollens to $s \rightarrow \lnot w$ to conclude therefore $w$, as that is not equivalent to Modus Tollens.

That said:

  • If you had $w$, you could deduce therefore $\lnot\lnot w$, and by Modus Tollens, get $\lnot s$, (by $\lnot \lnot w$ and premise (5), with Modus Tollens); but why would you want to do that? already have $\lnot s$!
  • One other point: you could have actually constructed the 5th premise from the first 4 premises, along with your subsequent deduction of $\;\lnot s$. For example:

7) $\lnot s\qquad\qquad\qquad$(...reasoning above)
7+) $\lnot s \lor \lnot w\quad\;$ (Disjunction Introduction/Addition from (7): that is, if we have established
$\qquad\qquad\qquad\qquad\quad\lnot s$, then we've established $\lnot s \lor $(anything))
5) $s \rightarrow \lnot w\qquad\;$ (Given (7+) and the fact that $\lnot s \lor \lnot w \equiv s \rightarrow \lnot w$).

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.